Analysis of the Interaction between Dividend Policy and Firm Performance in Manufacturing Sector - Singh Jha, Shankar Kumar; Aziz, Usama (Information Management and Business Review, 2019)
The purpose of this study is to investigate internal determinant factors of dividend policy in manufacturing firms. The study considers the impact of dividend payout ratio, signalling, earnings per share and risk on firm performance. This research also tries to create a link between dividend policy and firm performance. In the same way, the research is also aimed to create a link between these factors. Such as, the current link between the dividend policy and firm performance. It will elaborate this through current and previous studies as a whole. This study used primary data from the listed manufacturing firms in order to check the effects of dividend policy on firm performance. Data was collected from the primary source. The survey questionnaire was used to collect data from top management in order to highlight the impact of dividend policy on firm performance. Multi-regression analyses were undertaken to identify attributes that influence dividend policy. The results of the study demonstrate that all the variables are significant thus they have a positive impact on firm performance. The study established the findings that dividend payout, earning per share, signalling and risk positively and significantly influence the firm’s value. Moreover, companies should consider dividend policy in order to make the financial decision more efficiently. This study tells us that decisions about dividend policy should be made by considering other variables. The study has both practical and theoretical implication for top management in order to consider the dividend policy and its impact on firm performance.